The key role of market orientation in innovation ambidexterity in agribusiness firms - Corchuelo Martínez-Azúa, B.; Dias, Á.; Sama-Berrocal, C. (Review of Managerial Science, 2025)
The objective of this study is to examine the relationships between market orientation, organizational culture, proactive management, organizational climate, and organizational structure on the innovative orientation (exploitative and exploratory innovation). Little research has been conducted to examine the relationship between these organizational dimensions and innovation orientation. This study offers this and provides a particular type of companies (agribusiness) and context (Extremadura, Spain). Quantitative approach, by using structural modelling equations, to analyze data from 151 innovative agri-food firms was used in this study. Then, using a fuzzy set qualitative comparative analysis (fsQCA), was carried out to obtain additional insights. The main result find that market orientation plays a key role both in exploitative and exploratory innovation in agribusiness firms. Innovation exploitation is influenced by the firm’s organic structure. Results from fsQCA provide valuable findings showing that innovation exploitation and exploration result from distinct organizational configurations, thus providing valuable insights for decision and policy-making.